Indeks Pembangunan Manusia Pertumbahan Ekonomi dan Tingkat Kemiskinan di Pulau Sumatera - Muhammadinah - (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2022)
This study aims to determine the effect of the Human Development Index (HDI) and Economic Growth either partially or simultaneously on the Poverty Level on the island of Sumatra. The population and samples in this study were all provinces on the island of Sumatra. The data analysis technique used in this research is multiple regression and hypothesis testing using t test and F test using the Eviews program. The results showed that the variable Human Development Index (HDI) and economic growth either partially or simultaneously had a significant and significant effect on the poverty level on the island of Sumatra.